Is It Possible to Tackle Youth Needs with Agricultural and Rural Development Policies? - Mujčinović, Alen; Nikolić, Aleksandra; Tuna, Emelj; Stamenkovska, Ivana Janeska; Radović, Vesela; Flynn, Paul; McCauley, Veronica (MDPI AG, 2021)
Rural youth are influenced by a wide range of uncertainties regarding their personal and professional development. Rural youth and in particular rural NEETs (Not in Employment, Education or Training) are especially vulnerable and face higher risks of labour market, social and economic exclusion. This paper aims to analyse the determinants of the dynamics of rural NEETs in three post-transitional countries (Bosnia and Herzegovina, North Macedonia and Serbia) compared to the EU-28 average and to Ireland as an example of an established EU member state with over 50% of its population living in rural areas that can act as a benchmark for effective policy implementation to address challenges of marginalized youth, during the 2009–2019 period. The dynamics of rural NEET status and the efficiency/adaptability of regional development policies are revealed through analysis of macro and socioeconomic factors as well as specific employment-related indicators disaggregated by gender and degree of urbanisation. The comparative analysis indicates deficiencies in regional development policies among post-transitional countries and the potential to adapt modern European practices and policies for improving the rural NEETs’ position.